ANALISA ASBAB AL-NUZUL AL-WAHIDI DAN AL-SUYUTI Pada Al-Nur 3 dan Al-Furqan 68-70 - Muhammad Najib (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2013)
Asbab al-nuzul is one important instrument to holistically understand Qurâ€™an verses. This study was intended to recognize the character of asbab al-nuzul by al-Wahidi and LubÄb al-NuqÅ«l by Jalaluddin al-Suyuti, as well as to elaborate the implications of asbab al-nuzul to the meaning of Al-NÅ«r 3 and Al-Furqan 68-70. The asbab al-nuzul history of the both books would be positioned as the initial information to be later verified and analyzed. The analized and verified history became an instrument to review the meaning of the verses in asbab al-nuzul case. The above process could simultaneously provide a preliminary view of the character of AsbÄb al-NuzÅ«l al-WÄhidÄ« and LubÄb al-NuqÅ«l Jalaluddin al-SuyÅ«á¹Ä«.